2004
DOI: 10.1121/1.1772395
|View full text |Cite
|
Sign up to set email alerts
|

Chronic excitotoxicity in the guinea pig cochlea induces temporary functional deficits without disrupting otoacoustic emissions

Abstract: Brief cochlear excitotoxicity produces temporary neural swelling and transient deficits in auditory sensitivity; however, the consequences of long-lasting excitotoxic insult have not been tested. Chronic intra-cochlear infusion of the glutamate agonist AMPA (a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) resulted in functional deficits in the sound-evoked auditory brainstem response, as well as in behavioral measures of hearing. The electrophysiological deficits were similar to those observed following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 63 publications
3
27
0
1
Order By: Relevance
“…Hearing loss has been associated with the swollen afferent dendrites under IHCs as in mice lacking the glutamate transporter GLAST after sound exposure, in chinchillas after kainic acid excitotoxicity, in guinea pigs after sound exposure, and after intra-cochlear infusion of the aminoglycoside antibiotic amikacin and the glutamate agonist AMPA (␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) (Robertson, 1983;Zheng et al, 1997;Puel et al, 1998;Duan et al, 2000;Hakuba et al, 2000;Le Prell et al, 2004). Studies have also shown that functional recovery corresponds to structural recovery or reestablishment of the IHC/auditory-nerve synapse after acute excitotoxic-drug exposures (Zheng et al, 1997;Pujol and Puel 1999;X.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hearing loss has been associated with the swollen afferent dendrites under IHCs as in mice lacking the glutamate transporter GLAST after sound exposure, in chinchillas after kainic acid excitotoxicity, in guinea pigs after sound exposure, and after intra-cochlear infusion of the aminoglycoside antibiotic amikacin and the glutamate agonist AMPA (␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) (Robertson, 1983;Zheng et al, 1997;Puel et al, 1998;Duan et al, 2000;Hakuba et al, 2000;Le Prell et al, 2004). Studies have also shown that functional recovery corresponds to structural recovery or reestablishment of the IHC/auditory-nerve synapse after acute excitotoxic-drug exposures (Zheng et al, 1997;Pujol and Puel 1999;X.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that noise-induced hearing loss may be caused, in part, by excitotoxicity of SGNs. The excitotoxic damage to SGN is suggested by massive swelling of afferent dendrites under IHCs (Liberman and Mulroy, 1982;Robertson, 1983;Puel et al, 1998;Le Prell et al, 2004). To further test the hypothesis that NFB activity plays an important role in maintaining Ca 2ϩ homeostasis and protecting SGNs from excitotoxic injury, we examined the expression of calcium-buffering proteins and the profile of afferent dendrites under IHCs in wild-type (WT) and p50 Ϫ/Ϫ mice.…”
Section: Introductionmentioning
confidence: 99%
“…In the auditory system, auditory nerve degeneration may be a consequence of NTF deprivation that occurs when sensory cells in the organ of Corti are damaged. In the presence of intact hair cells, damaged auditory nerve peripheral processes will regrow and restore auditory sensation (Puel et al, 1991;Le Prell et al, 2004). However, with loss of hair cell targets, auditory nerve regrowth is minimal (Bohne and Harding, 1992;Strominger et al, 1995;Lawner et al, 1997;McFadden et al, 2004).…”
Section: Growth Factorsmentioning
confidence: 99%
“…The application of glutamate (Janssen et al, 1991) or glutamate agonists (Puel et al, 1991;Le Prell et al, 2004) results in functional deficits and swelling of auditory neurons equivalent to those observed after noise exposure (Robertson, 1983;Puel et al, 1998;Yamasoba et al, 2005). Large concentrations of glutamate are released in response to loud noise, and toxic concentrations of this excitatory amino acid lead to large sodium and potassium ion flux across the post-synaptic membranes and passive entry of chlorine; this osmotic imbalance results in entry of fluid into cells which in turn produces swelling, and ultimately, rupturing of cell membranes and degeneration (for review, see Le Prell et al, 2001).…”
Section: Glutamate Excitotoxicitymentioning
confidence: 99%
“…Threshold, tested separately for each ear, was defined as the lowest intensity of stimulation that yielded a repeatable waveform based on an identifiable ABR wave III or IV. ABR wave III is the most robust component of the guinea pig waveform [87,88].…”
Section: Auditory Brainstem Responsesmentioning
confidence: 99%